2015
DOI: 10.1590/1809-4430-eng.agric.v35n1p51-62/2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of companion ion on nitrate displacement through transport parameters analysis

Abstract: ABSTRACT:Nitrate is the main form of nitrogen associated with water contamination; the high mobility of this species in soil justifies the concern regarding nitrogen management in agricultural soils. Therefore, the objective of this research was to assess the effect of companion cation on nitrate displacement, by analyzing nitrate transport parameters through Breakthrough Curves (BTCs) and their settings made by numerical model (STANMOD). The experiment was carried out in the Soil and Water Quality Laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
1
0
4
Order By: Relevance
“…This discrepancy must have been due to the low concentrations of potassium used here, besides the lower concentrations of other ions in the used effluent when compared to vinasse. Silva et al (2015) analyzed the influence of counter ions (calcium and ammonium) on nitrate-anion transport parameters in deformed samples of two soils (Red Nitosol and Red-yellow Latosol). Their results showed that both counter ions had no influence on nitrate mobility through the soil columns.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy must have been due to the low concentrations of potassium used here, besides the lower concentrations of other ions in the used effluent when compared to vinasse. Silva et al (2015) analyzed the influence of counter ions (calcium and ammonium) on nitrate-anion transport parameters in deformed samples of two soils (Red Nitosol and Red-yellow Latosol). Their results showed that both counter ions had no influence on nitrate mobility through the soil columns.…”
Section: Resultsmentioning
confidence: 99%
“…O nitrogênio é um composto de grande importância para o crescimento das plantas, porém, em determinadas condições, é convertido em nitrato, o qual pode ser absorvido pelas plantas ou lixiviado para a água subterrânea após a ocorrência de chuva pesada ou irrigação intensa (RICO-GARCÍA et al, 2009). A mobilidade do nitrato em solo está relacionada a fatores como a textura e umidade do solo e à sua disponibilidade, sendo assim, o nitrato se torna a principal forma de nitrogênio associada à contaminação dos reservatórios de água subterrânea devido a atividades antropogênicas (SILVA et al, 2015). O VMP para este contaminante é de apenas 10,0 mg L -1 (USEPA, 1987).…”
Section: Manganêsunclassified
“…A mobilidade do nitrato em solo está relacionada a fatores como a textura e umidade do solo e à sua disponibilidade, sendo assim, o nitrato se torna a principal forma de nitrogênio associada à contaminação dos reservatórios de água subterrânea devido a atividades antropogênicas (SILVA et al 2015).…”
unclassified